HUBUNGAN KOGNITIF DAN AFEKTIF TERHADAP SELF REGULATION MELALUI MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION PADA MATERI ZAT ADITIF KELAS VIII MTs ISLAMIYAH GAJING TAHUN PELAJARAN 2022/2023 - Azhari Subakti, Dinda; Rosenta Purba, Ika; Dianti Siboro, Thiur (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the effect of cognitive and affective relationships on self-regulation using the Student Team Achievement Division learning model on additives in grade VIII of MTs Islamiyah Gajing in the 2022/2023 academic year. The population was 156 students, consisting of 5 classes, and the sample was taken using Cluster Random Sampling, resulting in two classes: experimental class 1 (VIII-3) with 32 students and experimental class 2 (VIII-4) with 32 students. Experimental class 1 was treated using the Student Team Achievement Division learning model, while experimental class 2 was treated using the Conventional learning model. Data analysis was performed by finding the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The results showed that the average post-test score for experimental class 1 was 85.03 and for experimental class 2 was 84.37, with a difference in learning outcomes of 0.66. The results of the hypothesis testing (t-test) obtained thitung (2.951) > ttabel (1.998) at a significance level of α = 0.05 and degrees of freedom (dk) = 62. Therefore, Ho is rejected and Ha is accepted. This means that there is a difference in the cognitive and affective relationship to self-regulation using the Student Team Achievement Division learning model on the additive substance material for class VIII MTs Islamiyah Gajing in the 2022/2023 academic year. It is concluded that there is a cognitive and affective relationship to self-regulation through the Student Team Achievement Division learning model on the additive substance material for class VIII MTs Islamiyah Gajing in the 2022/2023 academic year.